The Gut Microbiota of Healthy and Flavobacterium psychrophilum-Infected Rainbow Trout Fry Is Shaped by Antibiotics and Phage Therapies - Donati, Valentina Laura; Madsen, Lone; Middelboe, Mathias; Strube, Mikael Lenz; Dalsgaard, Inger (Frontiers in Microbiology, 2022)
In the aquaculture sector, there is an increased interest in developing environmentally friendly alternatives to antibiotics in the treatment and prevention of bacterial infections. This requires an understanding of the effects of different treatments on the fish microbiota as a measure for improving the fish health status. In this study, we focused on the freshwater pathogen Flavobacterium psychrophilum and investigated the effects of antibiotics (florfenicol) and phage therapies on the gut microbiota of healthy and infected rainbow trout fry (1-2 g). Florfenicol-coated feed was administered for 10 days starting two days after the infection procedure. A two component mix of phage targeting F. psychrophilum (FpV4 and FPSV-D22) was continuously delivered by feed with a prophylactic period of 12 days. Samples of the distal intestine were collected over time (day -1 and 1, 8 and 33 days post infection) and analyzed by community analysis targeting the 16S rRNA gene (V3-V4 region). Results showed the dysbiosis effect caused both by the infection and by florfenicol administration. Shifts in the overall composition were detected by β-diversity analysis, and changes in specific populations were observed during taxonomic mapping. Measures of α-diversity were only affected in infected fish (large variation observed 1 and 8 dpi). These community alterations disappeared again when fish recovered from the infection and the antibiotic treatment was terminated (33 dpi). Interestingly, phage addition altered the microbiota of the fish independently of the presence of their target bacterium. The overall gut bacterial community in fish fed phage-treated feed was different from the controls at each time point as revealed by β-diversity analysis. However, it was not possible to identify specific bacterial populations responsible of these changes except an increase of lactic acid bacteria 33 dpi. Overall, the results indicate that the administered phages might affect the complex network of phage-bacteria interactions in the fish gut. Nevertheless we did not observe negative effects on fish health or growth, further studies should be directed in understanding if these changes are beneficial or not for the fish health with an additional focus on the host immune response.